Graphene / silver composite conductive paste for HJT solar cell and preparation method and application of graphene / silver composite conductive paste

A three-dimensional conductive network of graphene/silver composite paste for HJT solar cells, prepared via liquid-assisted exfoliation and planetary stirring, addresses conductivity and printability issues, enhancing performance and reducing costs.

CN119230159APending Publication Date: 2024-12-31LANZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411185041.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing graphene/silver composite pastes for HJT solar cells suffer from poor conductivity, dispersibility, high sintering temperature, and printability, failing to harness the excellent intrinsic conductive properties of graphene.

Method used

A three-dimensional conductive network is constructed using zero-silver nanoparticles and two-dimensional graphene sheets, prepared through a method involving liquid-assisted physical turbulent exfoliation and three-stage planetary stirring, maintaining the integrity of graphene's lattice structure and enhancing conductivity.

Benefits of technology

The resulting graphene/silver composite conductive paste exhibits excellent printability and conductivity, reducing optical and electrical losses in HJT solar cells, achieving performance comparable to pure photovoltaic silver pastes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230159A_ABST
    Figure CN119230159A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solar cells, and particularly discloses graphene / silver composite conductive paste for an HJT solar cell and a preparation method and application of the graphene / silver composite conductive paste. The high-conductivity graphene slurry with a complete two-dimensional lattice structure is prepared by adopting a liquid phase assisted physical turbulence stripping method, then silver nanoparticles and graphene are self-assembled under the induction of organic molecule functional groups, and the silver nanoparticles are driven to be attached to the surfaces of two-dimensional graphene nanosheets by virtue of weak interaction of molecular chains. And constructing a three-dimensional conductive network with point-surface combination of zero-dimensional silver nanoparticles and two-dimensional graphene sheets, and preparing the high-conductivity graphene / silver paste composite conductive paste synergistically enhanced by two conductive agents. The composite conductive paste has excellent printability and aging resistance, a grid line electrode silk-screen-printed on an HJT solar cell silicon wafer has a large aspect ratio, the conductivity of the composite conductive paste and pure photovoltaic silver paste are in the same order of magnitude, and optical loss and electrical loss in photovoltaic power generation conversion efficiency are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of HJT solar cell materials, and specifically relates to a graphene / silver composite conductive paste for HJT solar cells, and a preparation method and application thereof. Background Art

[0002] The grid electrode prepared by screen printing is a key component of solar cells. Its function is to extract and collect the charges generated by the photoelectric effect, connect the external circuit, generate current, and thus achieve the purpose of photovoltaic power generation. Photovoltaic low-temperature curing silver paste is the raw material for preparing solar cell grid electrodes. It is a conductive mixture composed of high-purity (99.9%) metallic silver, organic resin, organic solvent, etc. It is the core material of photovoltaic cells, accounting for 10%-11% of the cost, while the new generation of HJT cells, its cost accounts for about 24%. Therefore, the cost of low-temperature silver paste manufacturing can be reduced through new technologies or new materials, thereby reducing the production cost of photovoltaic solar cell modules.

[0003] Selecting non-precious metal nanomaterials as conductive fillers to prepare composite silver pastes to reduce the silver content in photovoltaic silver pastes while maintaining excellent electrical and printing properties is an effective strategy to reduce the production cost of photovoltaic silver pastes. 2 The hybrid form is closely arranged, presenting a crystalline material with a two-dimensional (2D) honeycomb structure with a single atomic layer thickness. The unique lattice structure gives graphene various excellent properties. The theoretical specific surface area of ​​a single layer of defect-free graphene is 2630m 2 ·g -1 , the theoretical conductivity can reach 106S·m -1 , the carrier mobility can reach 15000cm 2 V -1 s -1 , thermal conductivity is 5300Wm -1 k -1 The above characteristics, especially high electrical conductivity, thermal conductivity, and stability in thermal environment and oxygen atmosphere, highlight unparalleled advantages in wire circuits, electronic component electrodes, high-precision welding electrodes and contact materials. If graphene can replace 10-30% of the silver content of low-temperature silver paste, according to the current growth scale of the photovoltaic market, it will save nearly 10 billion yuan each year.

[0004] The composite conductive paste made from the combination of graphene and silver paste has received widespread attention from all walks of life. However, due to the preparation process technology, the conductivity of the existing graphene / silver paste composite paste is quite different from that of pure silver paste, and the overall performance is poor. It does not reflect the excellent intrinsic conductive properties of graphene. At the same time, it has the shortcomings of poor dispersibility, high sintering temperature and poor printability. It is necessary to adopt new methods in the process preparation technology to regulate the components of the composite silver paste and the proportion of each component. Summary of the invention

[0005] The purpose of the present invention is to provide a graphene / silver composite conductive paste for HJT solar cells and its preparation method and application in view of the above-mentioned deficiencies in the prior art. A three-dimensional conductive network combining zero-silver nanoparticles and two-dimensional graphene sheets is constructed, and a highly conductive graphene / silver composite conductive paste synergistically enhanced by two conductive agents is prepared.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] The first object of the present invention is to provide a graphene / silver composite conductive paste for HJT solar cells, wherein the graphene / silver composite conductive paste comprises, by weight fraction, 5 to 20 parts of graphene, 50 to 70 parts of photovoltaic silver paste, 1 to 2.5 parts of adhesive, 5 to 15 parts of organic solvent, 0.5 to 2 parts of dispersant and 0.1 to 2.5 parts of active diluent.

[0008] The method for preparing the composite conductive paste comprises the following steps:

[0009] S1. Preparation of graphene nanosheets: weigh a certain amount of flake graphite powder and a dispersant, add them to an organic solvent, stir them evenly, and use an in-situ method to obtain a graphene dispersion by liquid-assisted physical turbulence exfoliation technology; the graphene particle size in the graphene dispersion is 5 to 15 μm, and the sheet thickness is not more than 3 nm;

[0010] S2, preparing graphene slurry, subjecting the graphene dispersion to ultrasonic-assisted dispersion treatment, and then concentrating it in a constant temperature water bath to obtain graphene slurry;

[0011] S3, preparation of graphene / silver composite slurry, weighing a certain amount of photovoltaic silver paste, adhesive, and active diluent according to the ratio, adding them to the graphene slurry, adopting three-stage planetary stirring, and finally obtaining the graphene / silver composite slurry; the photovoltaic silver paste has a solid content of 70-90%, and the silver particles are spherical and / or flaky, with a microscopic size of 100nm to 4μm.

[0012] Furthermore, the particle size of the flake graphite is 100 to 2000 meshes.

[0013] Furthermore, the adhesive is one or more of epoxy resin, polyacrylic resin, chloroacetic resin, polyurethane, and modified cellulose.

[0014] Furthermore, the organic solvent is one or more of anhydrous ethanol, terpineol, N-methylpyrrolidone, N,N-dimethylformamide, and nylon acid dimethyl ester.

[0015] Furthermore, the dispersant is one or more of ethyl cellulose, polyvinyl pyrrolidone, polyvinyl alcohol, and sodium carboxymethyl cellulose.

[0016] Furthermore, the active diluent is one or more of butyl carbitol, acetate, diethylene glycol, ethylene glycol, and diethylene glycol butyl ether acetate.

[0017] Furthermore, in step S1, the liquid phase shear stripping conditions are: high-speed stripping at 2000 rpm for 4 to 32 hours at room temperature and pressure.

[0018] Furthermore, the solid content of the graphene slurry prepared in step S2 is 200 to 800 mg / mL.

[0019] Furthermore, in step S3, the rotation speed of the three-stage centrifugal stirring is 500-2500 rpm.

[0020] The second object of the present invention is to provide the use of the composite conductive paste in preparing grid lines of solar cells.

[0021] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0022] (1) The graphene used in the present invention is a graphene slurry obtained in a low surface tension solvent system by means of the steric hindrance effect of a polymer long-chain dispersant and the action of a π-π or CH-π interface. The graphene is prepared by an in-situ method using a liquid-assisted physical turbulent exfoliation technique. Compared with reduced graphene oxide, this preparation method maintains the integrity of the two-dimensional lattice structure and excellent electrical properties of graphene. The polymer long-chain dispersant is adsorbed on the graphene nanosheets through the action of a π-π or CH-π interface, and the steric hindrance effect is used to induce intercalation between graphene sheets, giving the graphene slurry excellent dispersion stability.

[0023] (2) The graphene / silver composite slurry prepared by the present invention is a 3D conductive network of silver nanoparticles and graphene self-assembled under the induction of organic molecular functional groups, and the silver particles are driven to attach to the surface of the two-dimensional graphene nanosheets or embed between the graphene sheets by the weak interaction of the molecular chains, which prevents the secondary stacking of the graphene nanosheets under the action of van der Waals forces. At the same time, the high specific surface area of ​​graphene has excellent barrier properties, forming a passivation layer to prevent AgNPs from oxidizing. A three-dimensional conductive network of zero silver nanoparticles and two-dimensional graphene sheets is constructed, and a high-conductivity graphene / silver composite conductive slurry synergistically enhanced by two conductive agents is prepared.

[0024] (3) The process of preparing the graphene / silver composite slurry of the present invention is simple and does not involve the harsh reaction process required for the redox reaction, nor the complicated post-processing of preparing the composite silver slurry. It has excellent printability and aging resistance. The grid line electrode screen-printed on the HJT solar cell silicon wafer has a large aspect ratio, and the conductive performance is at the same order of magnitude as that of pure photovoltaic silver slurry, thereby reducing the optical loss and electrical loss in the photovoltaic power conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The SEM images of the graphene nanosheets provided by the present invention, in which a is an overall image of the graphene nanosheets at a scale of 100 μm, and b is an enlarged image of a certain nanosheet in a at a scale of 5 μm;

[0026] Figure 2 This is a SEM picture of the graphene / silver composite slurry provided by the present invention;

[0027] Figure 3 An optical picture of the grid electrode of the HJT solar cell provided by the present invention;

[0028] Figure 4 This is an optical picture of the line width test of the grid line electrode of the HJT solar cell provided by the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples and drawings. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.

[0030] The present invention provides a graphene / silver composite conductive paste for HJT solar cells. Specifically, the paste adopts a liquid-phase assisted physical turbulent exfoliation method to prepare highly conductive graphene with a complete crystal structure and its paste, then self-assembles silver nanoparticles and graphene under the induction of organic molecular functional groups, drives the silver particles to adhere to the surface of two-dimensional graphene nanosheets by means of weak interactions of molecular chains, constructs a three-dimensional conductive network of zero-dimensional silver nanoparticles and two-dimensional graphene sheets in point-to-surface combination, and prepares a highly conductive graphene / silver paste composite conductive paste synergistically enhanced by two conductive agents.

[0031] The present invention uses the prepared graphene / silver composite conductive paste to prepare the grid line electrode of the HJT solar cell sheet, and uses the screen printing technology to print the above graphene / silver composite paste on the HJT solar cell silicon wafer. The screen printing screen used is a 460-mesh stainless steel mesh with a designed line width of about 30 μm. After sintering in an oven at a temperature of 100 to 300° C. for 10 to 30 minutes, the screen-printed grid line electrode is firmly welded on the HJT cell silicon wafer, and an excellent ohmic contact is formed between the two, and the charge generated by the photoelectric effect is derived and collected, connected to the external circuit, and current is generated, thereby achieving the purpose of photovoltaic power generation.

[0032] The present invention provides a method for preparing a graphene / silver composite conductive paste for HJT solar cells, which mainly comprises the following steps:

[0033] S1. Preparation of graphene nanosheets: weigh 80-100g of graphite powder and 4-10g of dispersant, add them to anhydrous ethanol, stir for 6-12h to make it uniform, and prepare a graphite powder suspension. Use the in-situ method through liquid-assisted physical turbulent stripping technology, place the suspension in a turbulent stripping device, and strip at 2000rpm for 4-32h to obtain a graphene dispersion with a particle size of 5-15μm and a sheet thickness of less than 3nm. The dispersant is one or more of ethyl cellulose, polyvinyl pyrrolidone, polyvinyl alcohol, and sodium carboxymethyl cellulose;

[0034] S2, preparation of graphene slurry, subjecting the graphene dispersion to water bath ultrasonic assisted dispersion treatment for 30 to 60 minutes, and then concentrating it in a 75°C constant temperature water bath to obtain graphene slurry with a solid content of 200 to 800 mg / mL;

[0035] S3, preparation of graphene / silver composite slurry, weighing a certain amount of photovoltaic silver paste, adhesive, and active diluent according to the ratio, adding them to the graphene slurry, using three-stage planetary stirring for 10 minutes, and the speed of rotation is 500-2500rpm. Finally, the graphene / silver composite slurry is obtained. The active diluent is one or more of butyl carbitol, acetate, diethylene glycol, ethylene glycol, and diethylene glycol butyl ether acetate. The adhesive is one or more of epoxy resin, polyacrylic resin, chloroacetic resin, polyurethane, and modified cellulose.

[0036] It should be noted that, in the embodiment of the present invention, the photovoltaic silver paste is purchased from the market, and the model of the photovoltaic silver paste is DK61A (Wuxi Dike Electronic Materials Co., Ltd.).

[0037] Example 1

[0038] This embodiment provides a method for preparing a graphene / silver composite conductive paste for a HJT solar cell, comprising the following steps:

[0039] S1. Preparation of graphene nanosheets: 80 g of flake graphite and 4 g of polyvinyl pyrrolidone (PVP) were weighed and added to 1.5 L of anhydrous ethanol, and stirred for 12 h to make them uniformly dispersed to prepare a graphite powder suspension. The suspension was placed in a turbulent stripping device using an in-situ method through liquid-assisted physical turbulent stripping technology, and the stripping treatment was performed at 2000 rpm for 20 h to obtain a graphene dispersion with a particle size of about 5 μm and a sheet thickness of less than 2 nm;

[0040] S2, preparation of graphene slurry, subjecting the graphene dispersion to water bath ultrasonic assisted dispersion treatment for 30 min, and then concentrating it in a constant temperature water bath at 75° C. to obtain a graphene slurry with a solid content of 800 mg / mL;

[0041] S3, preparation of graphene / silver composite slurry, according to the mass ratio, weigh a certain amount of graphene slurry 10%, epoxy resin 2%, active diluent 1% (butyl carbitol: acetate: diethylene glycol = 1:1:1) and add them to photovoltaic silver paste, use three-stage planetary stirring for 10 minutes, the speed is 500, 1500, 2000 rpm, and the speed ratio is 1:1. Finally, the graphene / silver composite slurry is obtained.

[0042] The graphene / silver composite slurry prepared in the present invention is used to make a HJT solar cell grid line electrode to perform an electrical performance test and a line width test. The specific operation is as follows:

[0043] (1) The graphene / silver composite slurry is printed on the HJT solar cell silicon wafer using a screen printing process. The screen printing screen used is a 460-mesh stainless steel mesh with a design line width of about 30 μm.

[0044] (2) Take 40 mL of graphene / silver composite slurry and place it on the above screen printing screen, printing speed = 50 mm·s -1 The ink scraper and the screen are tilted at an angle of about 30°, and the scraper height is set 30μm below the actual substrate to achieve appropriate printing pressure. Sintering treatment is carried out in an oven at a temperature of 100-300℃ for 10-30min to firmly weld the screen-printed grid electrode on the HJT cell silicon wafer.

[0045] (3) Electrical performance test and line width test: The gate line electrode of the HJT solar cell prepared in this embodiment is tested for the gate line body resistivity and gate line width by a four-probe tester and an optical microscope.

[0046] Example 2

[0047] This embodiment provides a method for preparing a graphene / silver composite conductive paste for HJT solar cells, comprising the following steps:

[0048] S1. Preparation of graphene nanosheets: 80 g of flake graphite and 8 g of ethyl cellulose were weighed and added to 1.5 L of anhydrous ethanol, and stirred for 12 h to make them uniformly dispersed to prepare a graphite powder suspension. The suspension was placed in a turbulent stripping device using an in-situ method through liquid-assisted physical turbulent stripping technology, and the stripping treatment was performed at 2000 rpm for 20 h to obtain a graphene dispersion with a particle size of 10 μm and a sheet thickness of less than 3 nm;

[0049] S2, preparation of graphene slurry, subjecting the graphene dispersion to water bath ultrasonic assisted dispersion treatment for 30 min, and then concentrating it in a constant temperature water bath at 75° C. to obtain a graphene slurry with a solid content of 600 mg / mL;

[0050] S3, preparation of graphene / silver composite slurry, according to the mass ratio, weigh a certain amount of graphene slurry 10%, polypropylene resin 2%, active diluent 0.5% (butyl carbitol: acetate: diethylene glycol = 1:1:1) and add them to photovoltaic silver paste, use three-stage planetary stirring for 10 minutes, the speed is 500, 1500, 2000 rpm, and the speed ratio is 1:1. Finally, the graphene / silver composite slurry is obtained.

[0051] Example 3

[0052] This embodiment provides a method for preparing a graphene / silver composite conductive paste for a HJT solar cell, comprising the following steps:

[0053] S1. Preparation of graphene nanosheets: 80 g of flake graphite and 8 g of polyvinyl alcohol (PVA) were weighed and added to 1.5 L of anhydrous ethanol, and stirred for 12 h to make them uniformly dispersed to prepare a graphite powder suspension. The suspension was placed in a turbulent stripping device using an in-situ method through liquid-assisted physical turbulent stripping technology, and the stripping treatment was performed at 2000 rpm for 20 h to obtain a graphene dispersion with a particle size of 10 μm and a sheet thickness of less than 3 nm;

[0054] S2, preparation of graphene slurry, subjecting the graphene dispersion to water bath ultrasonic assisted dispersion treatment for 30 min, and then concentrating it in a constant temperature water bath at 75° C. to obtain a graphene slurry with a solid content of 450 mg / mL;

[0055] S3, preparation of graphene / silver composite slurry, according to the mass ratio, weigh a certain amount of graphene slurry 10%, chlorovinyl resin 2%, active diluent 1% (butyl carbitol: acetate: diethylene glycol = 1:1:1) and add them to photovoltaic silver paste, use three-stage planetary stirring for 10 minutes, the speed is 500, 1500, 2000 rpm, and the speed ratio is 1:1. Finally, the graphene / silver composite slurry is obtained.

[0056] Example 4

[0057] This embodiment provides a method for preparing a graphene / silver composite conductive paste for a HJT solar cell, comprising the following steps:

[0058] S1. Preparation of graphene nanosheets: 80 g of flake graphite was weighed and added to 1.5 L of anhydrous ethanol, and stirred for 12 h to make it uniformly dispersed to prepare a graphite powder suspension. The suspension was placed in a turbulent stripping device using an in-situ method through liquid-assisted physical turbulent stripping technology, and stripped at 2000 rpm for 20 h to obtain a graphene dispersion with a particle size of 15 μm and a sheet thickness of about 10 nm;

[0059] S2, preparation of graphene slurry, subjecting the graphene dispersion to water bath ultrasonic assisted dispersion treatment for 30 min, and then concentrating it in a constant temperature water bath at 75° C. to obtain a graphene slurry with a solid content of 350 mg / mL;

[0060] S3, preparation of graphene / silver composite slurry, according to the mass ratio, weigh a certain amount of graphene slurry 10%, polyurethane 4%, active diluent 1% (butyl carbitol: acetate: diethylene glycol = 1:1:1) and add them to photovoltaic silver paste, use three-stage planetary stirring for 10 minutes, the speed is 500, 1500, 2000 rpm, and the speed ratio is 1:1. Finally, the graphene / silver composite slurry is obtained.

[0061] Comparative Example 1

[0062] The comparative sample is a viscous, high-purity, 90% solid content conductive silver paste (purchased from Changzhou Juhe New Materials Co., Ltd.) consisting of metallic silver particles, adhesives, solvents, and additives.

[0063] The graphene / silver composite pastes prepared in Examples 1 to 4 and Comparative Example 1 and commercial photovoltaic silver paste were screen-printed into HJT solar cell grid electrodes, the sintering conditions were 100°C, 150°C, 200°C, 250°C, 300°C, and the curing time was 30 minutes, and finally a grid electrode with a line width of about 40 μm was obtained. The graphene composite silver paste grid electrode printed on the silicon wafer substrate was selected as the test object and compared with the commercial photovoltaic silver paste. The test results are shown in Table 1.

[0064] Table 1. Test results table.

[0065]

[0066]

[0067] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A graphene / silver composite conductive paste for HJT solar cells, characterized in that: The graphene / silver composite conductive paste comprises, by weight, 5 to 20 parts of graphene dispersion, 50 to 70 parts of photovoltaic silver paste, 1 to 2.5 parts of adhesive, 5 to 15 parts of organic solvent, 0.5 to 2 parts of dispersant and 0.1 to 2.5 parts of active diluent. The preparation method of the composite conductive paste comprises the following steps: S1. Preparation of graphene nanosheets: weigh a certain amount of flake graphite powder and a dispersant, add them to an organic solvent, stir them evenly, and use an in-situ method to obtain a graphene dispersion by liquid-assisted physical turbulence exfoliation technology; the graphene particle size in the graphene dispersion is 5 to 15 μm, and the sheet thickness is not more than 3 nm; S2, preparing graphene slurry, subjecting the graphene dispersion to ultrasonic-assisted dispersion treatment, and then concentrating it in a constant temperature water bath to obtain graphene slurry; S3, preparation of graphene / silver composite slurry, weighing a certain amount of photovoltaic silver paste, adhesive, and active diluent according to the ratio, adding them to the graphene slurry, adopting three-stage planetary stirring, and finally obtaining the graphene / silver composite slurry; the photovoltaic silver paste has a solid content of 70-90%, and the silver particles are spherical and / or flaky, with a microscopic size of 100nm to 4μm.

2. The graphene / silver composite conductive paste according to claim 1, characterized in that: The particle size of the flake graphite is 100 to 2000 meshes.

3. The graphene / silver composite conductive paste according to claim 1, characterized in that: The adhesive is one or more of epoxy resin, polyacrylic resin, chloroacetic resin, polyurethane and modified cellulose.

4. The graphene / silver composite conductive paste according to claim 1, characterized in that: The organic solvent is one or more of anhydrous ethanol, terpineol, N-methylpyrrolidone, N,N-dimethylformamide and nylon acid dimethyl ester.

5. The graphene / silver composite conductive paste according to claim 1, characterized in that: The dispersant is one or more of ethyl cellulose, polyvinyl pyrrolidone, polyvinyl alcohol, and sodium carboxymethyl cellulose.

6. The graphene / silver composite conductive paste according to claim 1, characterized in that: The active diluent is one or more of butyl carbitol, acetate, diethylene glycol, ethylene glycol, and diethylene glycol butyl ether acetate.

7. The graphene / silver composite conductive paste according to claim 1, characterized in that: In step S1, the liquid phase shear stripping conditions are: high-speed stripping at 2000 rpm for 4 to 32 hours at room temperature and pressure.

8. The graphene / silver composite conductive paste according to claim 1, characterized in that: The solid content of the graphene slurry prepared in step S2 is 200-800 mg / mL.

9. The graphene / silver composite conductive paste according to claim 1, characterized in that: In step S3, the rotation speed of the three-stage centrifugal stirring is 500-2500 rpm.

10. Use of the composite conductive paste according to any one of claims 1 to 9 in preparing grid lines of solar cells.

Citation Information

Patent Citations

  • Method of preparing graphene nanoplate, prepared graphene nanoplate, graphene nanoplate paste, and conductive layer including the graphene nanoplate

    CN104555995A

  • Preparation of intermediate-temperature graphene / silver composite conductive slurry and application thereof

    CN108305702A

  • Preparation method of graphene conductive slurry and prepared conductive coating

    CN108305716A

  • Composite aqueous graphene conductive paste and preparation method thereof

    CN111403082A

  • Preparation method of nano-silver conductive ink

    CN113234360A